Sinomenine ameliorates cardiac hypertrophy by activating Nrf2/ARE signaling pathway. Issue 2 (20th December 2021) - Yuan, ManLi; Zhao, Bei; Jia, Huaping; Zhang, Can; Zuo, Xiaowen
ABSTRACT: Cardiac hypertrophy (CH) is a result of the physiological adaptation of the heart to coronary heart disease, hypertension, and other cardiovascular diseases. Sinomenine is extracted from Caulis Sinomenii . This study aimed to explore the specific mechanism of the action of sinomenine in cardiac hypertrophy (CH) via Nrf2/ARE signaling pathway in vivo and in vitro . To establish a model of CH, H9C2 cells were treated with angiotensin II (Ang II) and intraperitoneally injected with isoproterenol. Then the cells were treated with 50 and 100 μM sinomenine. TUNEL, HE, rhodamine-labeled phalloidin, and immunohistochemical staining were performed. Flow cytometry was used to measure apoptosis rates. mRNA expression of ANP, BNP, and β-MHC was determined by qRT-PCR. Furthermore, western blotting was performed to analyze protein expression. After sinomenine treatment, the surface area and apoptosis rates were decreased. Furthermore, the mRNA expression of ANP, BNP, and β-MHC, levels of reactive oxygen species and malondialdehyde, and protein expression of Caspase3 and Bax were down-regulated, and the protein expression of Bcl-2 was upregulated. Sinomenine activates the Nrf2/ARE signaling pathway, and inhibition of this signaling pathway reversed the effects of sinomenine. In animal experiments, sinomenine decreased the heart weight and left ventricular weight indices, as well as the expression of ANP, BNP, and β-MHC. Furthermore, sinomenine reduced the apoptosis rate and relieved CH-related oxidative stress by activating the Nrf2/ARE signaling pathway. Together, these findings reveal that sinomenine is a potential candidate drug for CH treatment and further research is required to generalize the result in human subjects.